1954
DOI: 10.1021/ac60093a025
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Synthetic Anionic Detergent Compositions

Abstract: In the manufacture of synthetic anionic detergents, it is desirable to obtain accurate control analyses of the product with a minimum expenditure of effort and time.The main ingredients of interest are active (sodium alkyl sulfates or alkylbenzenesulfonates), sodium sulfate and, occasionally, low molecular weight sulfonate additives such as benzene-H, toluene-A, and xylenesulfonates. In addition, color of the product is quite important from the standpoint of quality control. Epton's quaternary titration proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1956
1956
1970
1970

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Carbon has been reported as an adsorbent for alkyl benzenesulfonate (12,28,30), but under conditions giving quantitative desorption, the benzenesulfonate is not separated from all interfering materials. Alkyl benzenesulfonate can be extracted from hydrochloric acid solutions with chloroform (5) or ether (14), and the present authors found that it can be extracted from 3.6 " sulfuric acid with chloroform. In all these cases, however, the protein interference is increased, because reduction of the pH increases the anionic detergent binding power of proteins (4).…”
mentioning
confidence: 49%
“…Carbon has been reported as an adsorbent for alkyl benzenesulfonate (12,28,30), but under conditions giving quantitative desorption, the benzenesulfonate is not separated from all interfering materials. Alkyl benzenesulfonate can be extracted from hydrochloric acid solutions with chloroform (5) or ether (14), and the present authors found that it can be extracted from 3.6 " sulfuric acid with chloroform. In all these cases, however, the protein interference is increased, because reduction of the pH increases the anionic detergent binding power of proteins (4).…”
mentioning
confidence: 49%
“…Products containing ultraviolet absorbing materials such as sodium toluene or xylene sulfonates cannot be analyzed by the method because of their positive interference with alkyl aryl sulfonates. Although methods are available for removing interferences of this type (7), their use prior to analysis would increase analytical time to a point where the method would not be attractive for control purposes.…”
Section: Journal Of the Americanmentioning
confidence: 99%
“…High tool wt alkyl awl sulfonates (alkyl chain lengths of 4 carbons or more) can be separated from short chain sulfonates, such as toluene sulfonate, by extraction from an acidified aqueous solution with ethyl ether (16). The alkyl benzene sulfonate content of the ether layer nmy be determined by UV spectrophotometry (17) or by cationic titration (18,19).…”
Section: Separation Of High Mot Wt (Long Chain) Sulfonates From Low Mmentioning
confidence: 99%